An In-silico Simulation of Pressure Wave Excursions after Impact to the Frontal Lobe of a Homogenous Model of the Brain. Issue 2 (2020) - Smith, Nicole; Wright, Frederick; Docherty, Paul D.; Lilley, Rebecca; Kabaliuk, Natalia
Abstract: Traumatic impacts to the crania are known to have chronic effects on cerebral tissue and cognitive function. However, the inaccessibility of healthy brain tissue has limited studies of the mechanical behavior of the brain during impact. Consequently, it is uncertain how specific impacts lead to injury. The well-known Head Injury Criterion (HIC) metric is stochastic in nature. Therefore, it cannot provide deterministic indications of the severity of certain impacts and is ambivalent to trauma location. This research investigated an impact to the anterior region of an isomorphic model of intracranial tissue. The impact was 18 mm lateral of the sagittal plane. The impact propagation through the brain model was observed with a focus on the depth of wave penetration. The brain model was simplified by removing material property variations across white and grey matter and in the ventricles that contain cerebrospinal fluid regions. Ultimately, homogeneity of the simplified model was assumed to show more conservative results than what may be observed in practice. The simulation showed the significance of the initial impact magnitude and location with respect to any propagated wave. It was observed that despite minimizing the effect of damping in the model, pressure waves were not significant at the anterior of the brain. Thus, it was concluded that it is unlikely that secondary impact during TBI has a significant correlation to the location and severity of injury sustained.